Road Transportation and Legal Framework in Nepal - Lamichhane, Diamond (KDCBAR Law Journal, 2025)
This article investigates how road transportation interacts with international legal frameworks, particularly focusing on their impact on the movement of vehicles, goods, and individuals across borders. Utilizing Nepal as a case study, the research examines the nation’s road transport systems alongside international legal obligations and treaties that influence landlocked nations. It explores the significance of international agreements such as the Vienna Conventions concerning Road Traffic and Transit, the United Nations’ pacts on transport infrastructure, and regional initiatives like the South Asian Association for Regional Cooperation (SAARC) transport agreements. The analysis further evaluates how Nepal’s national transport regulations conform to or differ from these international standards, pinpointing gaps and challenges in legal alignment, infrastructure enhancement, and cross- border connectivity. Attention is directed towards matters of transit rights, foreign investment, safety regulations, and sustainable transportation. Through doctrinal analysis, case studies, and policy assessments, the dissertation offers suggestions for improving Nepal’s legal and institutional frameworks to bolster regional integration and facilitate safe, efficient, and lawful road transport in alignment with global standards.